Power markets with Renewables: New perspectives for the European Target Model - Karsten Neuhoff; Sophia Wolter; Sebastian Schwenen (The Energy Journal, 2016)
We discuss at the European example how power market design evolves with increasing shares of intermittent renewables. Short-term markets and system operation have to accommodate for the different needs of renewable and conventional generation assets and flexibility options. This can be achieved by pooling resources over larger geographic areas through common auction platforms, realizing the full flexibility of different assets based on multi-part bids while efficiently allocating scarce network resources. For investment and re-investment choices different technology groups like wind and solar versus fossil fuel based generation may warrant a different treatment - reflecting differing levels of publicly accessible information, requirements for grid infrastructure, types of strategic choices relevant for the sector and shares of capital cost in overall generation costs. We discuss opportunities for such a differentiated treatment while maintaining synergies in short-term system operation.
Keywords: Q41; Q42; D44; 330; Power market design; Regulation; Investment framework; Intermittent renewables